The Long-Term Health Benefits of Breastfeeding: Obesity Prevention, Metabolic Health, and Cardiovascular Protection - Lewandowska, Dominika; Rosińska-Lewandoska, Dominika; Ufnal, Julia; Szewczyk, Marcelina; Jarosz, Kinga; Wolff, Anna; Morawska, Maria; Gruszka, Szymon; Kożuchowska, Klaudia; Pilarz, Dawid (Journal of Education, Health and Sport, 2024)
Introduction: Recent research highlights a link between early dietary habits, especially breastfeeding, and reduced obesity risk in adulthood. Breastfeeding provides essential nutrients and compounds that may shape an infant’s metabolism. This article reviews current findings to guide parents in supporting lifelong healthy development. Material and Methods: This review examined 30 studies focusing on the relationship between breastfeeding and the risk of developing obesity. Relevant studies were identified through searches on PubMed and Google Scholar. Literature Analysis: The reviewed literature suggests a possible link between breastfeeding and a decreased likelihood of obesity in adulthood, although comprehensive, systematic research on this relationship is still scarce. Findings indicate that bioactive elements in breast milk and breastfeeding behaviors may play a role in early metabolic and appetite regulation, which could influence weight control later in life. Observational studies and case reports show varying impacts, often dependent on factors like the duration and exclusivity of breastfeeding, as well as broader environmental influences. Conclusions: Breastfeeding offers significant long-term health benefits, including reduced risks of obesity, type 2 diabetes, and cardiovascular diseases. Studies show that longer breastfeeding duration is associated with healthier weight trajectories, improved metabolic outcomes, and lower BMI and HDL levels later in life. Exclusive breastfeeding for six months or more provides substantial protection against obesity in childhood and adulthood. Early formula introduction is linked to higher BMI trajectories and increased metabolic risks. These findings emphasize the importance of promoting breastfeeding as a key public health strategy to support long-term health and disease prevention.